Adjustment of the MIND diet tool for discriminating Greek patients with dementia: A confirmatory factor analysis - Vassilopoulou, Emilia; Koumbi, Lemonica; Karastogiannidou, Calliope; Sotiriadis, Panagiotis Marios; Felicia, Pop Claudia; Tsolaki, Magda (Frontiers in Neurology, 2022)
Background: The MIND diet, a hybrid of the Mediterranean and DASH diets, has been shown to reduce cognitive decline and dementia occurrence. Aim: In the current cross-sectional study the effect of the MIND diet in elderly Greek individuals, assessed for cognitive decline, was investigated. Confirmatory factor analysis (CFA) evaluated the MIND diet score's factor structure in relation to the ability to distinguish the Greek elderly population diagnosed with or without dementia. Methods: One hundred fifteen participants recently diagnosed with dementia and 52 cognitively healthy controls, after proper neuropsychological testing by neurologists, were included. To ensure the variance-covariance of matrix for the CFA, a second reference group of 36 participants who self-reported as healthy in terms of cognitive status from the general Greek population, was included. Demographic, anthropometric characteristics, emotional status, cognitive function, and dementia diagnosis were recorded. A prediction model investigated the MIND diet’s components to separate the study participants according to their cognitive health. CFA was used to examine if the structure of the MIND diet tool scale was a proper model fit or if a different model more appropriately fit our sample data. Results and Discussion: The CFA conducted, suggested that the 9 components MIND diet score supported our sample data better than the original 15-item MIND diet. Conclusion: The MIND diets’ components must be considered in relevance to the dietary habits and cultural background of the respective population studied. Future studies should evaluate prospectively the effect of MIND-9 on preventing the onset of dementia in Greek adults.